Benefits of augmentative signs in word learning: Evidence from children who are deaf/hard of hearing and children with specific language impairment. (December 2016) - van Berkel-van Hoof, Lian; Hermans, Daan; Knoors, Harry; Verhoeven, Ludo
Graphical abstract: Highlights: Deaf and hard-of-hearing children retain words better if taught with augmentative signs. Typically developing children learn as many words with signs as without. The same is true for children with Specific Language Impairment. Abstract: Background: Augmentative signs may facilitate word learning in children with vocabulary difficulties, for example, children who are Deaf/Hard of Hearing (DHH) and children with Specific Language Impairment (SLI). Despite the fact that augmentative signs may aid second language learning in populations with a typical language development, empirical evidence in favor of this claim is lacking. Aims: We aim to investigate whether augmentative signs facilitate word learning for DHH children, children with SLI, and typically developing (TD) children. Methods and procedures: Whereas previous studies taught children new labels for familiar objects, the present study taught new labels for new objects. In our word learning experiment children were presented with pictures of imaginary creatures and pseudo words. Half of the words were accompanied by an augmentative pseudo sign. The children were tested for their receptive word knowledge. Outcomes and results: The DHH children benefitted significantly from augmentative signs, but the children with SLI and TD age-matched peers did not score significantly different on words from either the sign or no-sign condition. Conclusions and implications: These results suggest that using Sign-Supported speech in classrooms of bimodal bilingual DHH children may support their spoken language development. The difference between earlier research findings and the present results may be caused by a difference in methodology.